An automatic modeling approach for the potential evaluation of CO2 geological storage in the deep saline aquifer - Jing, Tieya; Fu, Jie; Zhou, Juan; Ma, Xin; Diao, Yujie; Liu, Ting; Fu, Lei; Guo, Jinxing (Frontiers in Energy Research, 2022)
Geological storage of carbon dioxide is receiving more and more attention as one of the efficient carbon reduction technologies, as China's carbon-neutral strategic plan moves forward. There is an increasing demand for more effective and thorough methodologies to assess the potential of CO2 storage in deep saline aquifers. This study proposes a method for evaluating the geological storage potential of CO2 in deep saline aquifers and constructs an automatic evaluation system for the comprehensive potential of CO2 geological storage using ArcGIS Model Builder visual modeling technology. The automatic evaluation system consists of four functional parts: information collating and database constructing, data pre-processing, model building evaluation and result validation evaluation. First, structured and unstructured data including underlying geology, tectonic geology, oil and gas geology, and drilling data are collated and established in a geodatabase. Second, pre-processing models of the deep saline reservoir-caprock data are established based on the analysis of the geological evolution history of the study area to determine the effective storage thickness, effective porosity, and the influence range of faults; kriging methods are then used to realize the spatial interpolation of the evaluation parameters. Third, the volume coefficient method is adopted to construct the underground storage space model and to establish the density distribution model of the supercritical CO2 with nonlinear function while taking into account four evaluation factors (i.e. area, effective porosity, effective thickness, effective coefficient) and two limiting factors (i.e. fault, burial depth). Finally, the geological storage potential of CO2 in the study area is evaluated with the classification of the potential level and compared with the numerical simulation results to verify the model's accuracy. The model is first applied in this paper using a suitable target in China as a case study. The results show that this target area's anticipated storage potential value reaches 52.557 Mt. The total precision error, according to a comparison of the numerical simulation results, is 8.20%. Based on the results obtained, it can be concluded that the automatic GIS-based modeling approach is suitable for a comparable study of potential evaluation of CO2 geological storage in deep saline aquifers.